Recent Advances of Beta Zeolite in the Volatile Organic Compounds(VOCs) Elimination by the Catalytic Oxidations - Cheng, Dajun; Meng, Xiangju (Chemical research in Chinese universities, 2022)
Volatile organic compounds(VOCs) have become one of the most serious threats to human health and eco-environment due to their volatility, toxicity and diffusivity, etc. Catalytic completely oxidation had been regarded as a highly efficient strategy for the VOCs abatement. Metal or metal oxides supported on zeolite have been considered as superior catalysts for the treatment of VOCs. Among them, Beta zeolites have attracted many attentions due to their unique structure and consequently catalytic properties in the oxidation of VOCs. The progresses and developments made in the understanding and design of Beta zeolites-based catalysts in the completely oxidation of VOCs in the past two decades have been systematically summarized in this review.